Diseminasi Transformasi Pendidikan untuk Menghadapi Tantangan Bonus Demografi kepada Guru-Guru di Kecamatan Buko - Kusno Setiadi; Suma K. Saleh; Khairul Akbar; Masrion Tahawali; Asraty Poku (Jurnal Pengabdian Masyarakat Indonesia (JPMI), 2024)
Community Service Activities (PKM) with the title "Dissemination of Educational Transformation to Face the Challenge of Demographic Bonuses to Teachers in Buko District" was carried out in September 2024 and involved 30 teachers from various schools. This activity aims to improve teachers' understanding and skills regarding 21st century education, especially in the use of technology and collaborative learning strategies. The training was carried out for two days using interactive lecture methods, group discussions, and simulations of 21st century learning practices. Evaluation was carried out through questionnaires to measure increased understanding and observation to assess skills in applying learning technology. The results showed significant improvement, with 60% of participants having excellent understanding after the training, up from 10% before the training. In addition, most participants were able to use interactive applications and media well, although there were still challenges in implementing group discussion strategies. This training is effective in supporting educational transformation, but further assistance is needed for collaborative aspects.